DETERMINAN NON PERFORMING FINANCING SEKTOR KONSTRUKSI PADA PERBANKAN SYARIAH PERIODE 2010 - 2017 - Agung Haryanto; Agus Kurniawan (Ekonomi Islam, 2018)
The aim of this research is to analyze the determinant of construction's non-performing financing in short-term and long-term. This research used Vector Error Correction Model (VECM). The result shows that in short-term CAR at the first until fourth lag, Inflation at the first until third lag, IPI at the first until third lag, and Foreign Debt at the third until fifth lag has a significantly positive effect to Construction's Non-Performing Financing. FDR at the third and fourth lag and Exchange Rate at the first lag have a significantly negative effect on Construction's Non-Performing Financing. Meanwhile, in long-term FDR, CAR, Inflation, and IPI have a significantly positive effect on Construction's Non-Performing Financing. Exchange Rate and Foreign Debt have no significant effect on Construction's Non-Performing Financing. Keywords: FDR, CAR, Inflation, IPI, Exchange Rate, Foreign Debt, Construction's Non-Performing Financing, VECM.